Response of oxidative stress and isoflavone treatment on superoxide dismutase enzyme activities and lipid peroxidation in rat’s liver - Suarsana IN; Wresdiyati T; Suprayogi A (Jurnal Ilmu Ternak dan Veteriner, 2013)
Oxidative stress is defined as over-production of free radicals which lead to cells damage, pathological condition and cell death. The objective of this study was to analyze respond of oxidative stress and isoflavone treatment on superoxide dismutase (SOD) enzyme activities and lipid peroxidation in rat liver. A total of fifteen male Spraque Dawley rats were used in this study. They were sub-divided into three groups; (1) a negative control group, (2) a stress oxidative group, and (3) treatment by stress condition followed by treatment with isoflavone. Stress condition was achieved by five days fasting together with swimming for 5 mins/day and only drinking water ad libitum. Isoflavone was orally administrated on a dose of 1 mg/200g bw/day for five days. At the end of the experiment, rats were sacrificed by anesthesia. Liver was collected for analysis of SOD enzyme activities, SOD immunohistochemical analysis, and malondialdehyde (MDA) level. Result showed that stress condition increase free radicals that showed by decreased SOD activity, and increased MDA level. Isoflavone treatment could get over reduction of SOD and prevented increase of MDA level in the liver of rats under stress conditions. Key Words: Oxidative Stress, Isoflavone, Rat, Superoxide Dismutase, Malondialdehyde